Learning in the early years, 3-7 - Riley, Jeni.; Sage eBooks (London : SAGE, 2007)
Addressing issues surrounding continuity, progression, subject, knowledge and age-phase specific pedagogies, this text helps early years teachers understand the nature, form and content of the curriculum for children aged 3-7 and the most appropriate ways of presenting it.
Previous ed.: published as Learning in the early years. London : Paul Chapman, 2003.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Early childhood education; Electronic books